2003
DOI: 10.1261/rna.5560903
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of domain structure to the RNA 3′ end processing and degradation functions of the nuclear exosome subunit Rrp6p

Abstract: The 3-5 riboexonuclease Rrp6p, a nuclear component of the exosome, functions with other exosome components to produce the mature 3 ends of 5.8S rRNA, sno-and snRNAs, and to destroy improperly processed precursor (pre)-rRNAs and pre-mRNAs. Rrp6p is a member of the RNase D family of riboexonucleases and displays a high degree of homology with the active site of the deoxyriboexonuclease domain of Escherichia coli DNA polymerase I, the crystal structure of which indicates a two-metal ion mechanism for phosphodiest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(99 citation statements)
references
References 34 publications
(64 reference statements)
6
92
1
Order By: Relevance
“…Rrp6 contains three domains required for nuclear localization, exoribonuclease activity, and RNA substrate specificity (43). Although a number of mRNAs are deregulated in the absence of Rrp6 (Dataset S2) it seems that protein-coding transcripts are recognized by the protein as substrates only in mutants that fail to export them from the nucleus (44).…”
Section: Rrp6 Function Is Important For the Transition From Mitosis Tmentioning
confidence: 99%
“…Rrp6 contains three domains required for nuclear localization, exoribonuclease activity, and RNA substrate specificity (43). Although a number of mRNAs are deregulated in the absence of Rrp6 (Dataset S2) it seems that protein-coding transcripts are recognized by the protein as substrates only in mutants that fail to export them from the nucleus (44).…”
Section: Rrp6 Function Is Important For the Transition From Mitosis Tmentioning
confidence: 99%
“…5 Structurefunction studies of Rrp6 proteins with point mutations in the exonuclease domain confirmed the two-metal ion mechanism and suggested that, like the exonuclease domains of DNA polymerases, Rrp6 utilizes a phenylalanine to stabilize the hydroxyl anion intermediate activated for phosphodiester bond cleavage. 6,7 Unlike Dis3/Rrp44, whose activity is attenuated by interaction with Exo9, Rrp6 retains its characteristic properties in the Exo11 complex. 8 Rrp6 contains two HRDC (Helicase RNaseD Cterminal) domains, only one of which was predicated by sequence homology.…”
Section: Structure and Activity Of Rrp6mentioning
confidence: 99%
“…The D238A single amino acid substitution disrupts the coordination of metal ions in the active site whereas the Y361A mutation prevents the activation of the hydrolytic water and thereby presumably abolishes exonucleolytic activity of the enzyme, while the D457A mutation in the conserved helicase and RNase D Cterminal (HRDC) domain alters protein interdomain contacts, possibly affecting coordination of the RNA substrate (Phillips and Butler 2003;Midtgaard et al 2006). In addition, deletion of the first 128 amino acids of Rrp6p has been shown to disrupt its interaction with Rrp47p (Stead et al 2007).…”
Section: In Vitro Characterization Of Rrp6p Mutantsmentioning
confidence: 99%